Working towards a framework for enhancing public e-procurement for Zimbabwe State Owned Enterprises (SOEs). - Dlakuseni. S; Kanyepe J; Tukuta. M (International Journal of Supply Chain Management, 2018)
E-Procurement is more than just a system for making purchases online. Some organisations implement e-procurement and succeed while others fail. This study was carried out to assess the potential of e-procurement in the public sector of Zimbabwe with State Owned Enterprises (SOEs) in focus. The objectives of the study were to establish the status quo of e-procurement in Zimbabwe public Procurement, identify major areas of e-procurement challenges, to establish being faced in Zimbabwe public procurement, and recommend a framework that enhances e-procurement in Zimbabwe. The research involved a case study of State-Owned Enterprises in Zimbabwe. A purposive sampling technique was adopted for the study and out of the target number of 60 respondents, 50 questionnaires were validly completed and returned. The collected data was analyzed using SPSS and Microsoft excel presented in tables and figures. From the study, it was revealed that employee competency, inadequate legal framework, inadequate technological infrastructure and security of procurement transaction data were challenges to e-Procurement adoption in the organizations under review. The study recommends continuous training of staff on e-Procurement. In addition, formal recognition backed by legislation of the electronic procurement transactions should be encouraged. Integration of the institutions system and those of the suppliers, demonstration of the positive impact of the systems, and installation of linkages between all Governments agencies should be encouraged.